Observasi Pembelajaran Sejarah Kebudayaan Islam di Madrasah Ibtidaiyah Nurul Iman Pematang Gajah Muaro Jambi - Yarisandi, Devi (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2021)
History of Islamic Culture (SKI) is one of the subjects studied at Madrasah Ibtidaiyah (MI), Madrasah Tsanawiyah (MTS) and Madrasah Aliyah (MA). Learning Islamic Cultural History (SKI) also has a very important role. This subject is presented by the teacher, including by referring to the textbook entitled History of Islamic Culture (SKI) for MI. This research was conducted aiming to find out about how the process of implementing Islamic Cultural History (SKI) learning for class VI students at Madrasah Ibtidaiyah Nurul Iman Pematang Gajah Kec, Jambi Outside the City, Kab. Muaro Jambi. To achieve maximum learning objectives, teachers are required to use appropriate methods, strategies and learning media.